Образование собственных дефектов в кристаллах CaF[2] при облучении ускоренными электронами - Чинков Е. П. Евгений Петрович; Яковлев В. Ю. Виктор Юрьевич; Лисицын В. М. Виктор Михайлович; Штанько В. Ф. Виктор Федорович (2003, 2003)
The effect of a temperature on defects formation has been studied by time-resolved optical spectroscopy. It is established what with increase of the temperature are created the an F-H-centers pair and the unknown defects. The picture of the this defects is discussed.